Genetic variation and heritability of resistance to Cinara cupressi in Cupressus lusitanica - Kamunya, S.M. (Moi Univ., P.O. Box 1125 Eldoret (Kenya). Dept. of Forestry) (2013)
Genetic variation and heritability of resistance to Cinara cupressi in Cupressus lusitanica. A study was undertaken to determine the genetic variation and heritability of resistance to Cinara cupressi in Cupressus lusitanica using half-sib and full-sib progeny trials aged 30 and 22 years respectively. There was considerable between-and within-family variations in aphid damage in both trials. The half-sib family heritability of 0.56 plus minus 0.21 and individual tree narrow-sense heritability of 0.45 plus minus 0.31 for half-and full-sibs respectively are high enough to indicate genetic influence in resistance which opens possibilities for effective selection and breeding for resistance. There were significant among-parent effects depicting strong general combining ability (p less than 0.01) while male x female interactions were negligible (p more than 0.05) indicating lack of specific combining ability effects. The genetic correlations between aphid damage and growth characters (height and diameter) were not significant (p more than 0.05) for either trials indicating that selection for resistance is not likely to have adverse effects on these economic traits. The presence of additive variance, and relatively high heritability in resistance within the progeny trials augur well for succesful incorporation of aphid resistance into the future breeds via seed orchards.